Improving physiological characteristics of Oryza sativa L. via sound wave stimulation - Faiznur 'Iffah Pydi,
The present study aimed to identify the changes in physiological characteristics of rice (Oryza sativa L) upon sound wave stimulation. Rice was grown at varying distance from a sound wave source which corresponded to specific sound quality in terms of hertz and decibel values. The plants were measured in terms of seedling germination, plant appearance, leaf physiology and stomatal properties. Sound wave at specific qualities resulted in improving certain parametres significantly such as number of tiller, photosynthetic rate and percentage of stomatal file but significantly decreasing the value of seed vigour index and stomatal pore area. The study aimed to find the 'sweet spot' to improve rice production via specific sound wave quality treatment. Depending on the condition of the rice cultivation, if water is abundant and never an issue, the sound qualities of 380Hz/78dB, 357Hz/69dB and 350Hz/60dB would result in relatively more vigorous rice plants due to high photosynthetic rate. But if water efficiency is the goal then sound quality of 359Hz/73dB is suggested for this purpose.